Effects of Liposomes Contained in Thermosensitive Hydrogels as Biomaterials Useful in Neural Tissue Engineering - Osorio-Lira, F (Multidisciplinary Digital Publishing Institute (MDPI), 2017)
Advances in the generation of suitable thermosensitive hydrogels for the delivery of cells in neural tissue engineering demonstrate a delicate relationship between physical properties and capabilities to promote cell proliferation and differentiation. To improve the properties of these materials, it is possible to add liposomes for the controlled release of bioactive elements, which in turn can affect the physical and biological properties of the hydrogels. In the present investigation, different hydrogels based on Pluronic F127 have been formulated with the incorporation of chitosan and two types of liposomes of two different sizes. The rheological and thermal properties and their relation with the neurite proliferation and growth of the PC12 cell line were evaluated. Our results show that the incorporation of liposomes modifies the properties of the hydrogels dependent on the concentration of chitosan and the lipid type in the liposomes, which directly affect the capabilities of the hydrogels to promote the viability and differentiation of PC12 cells. © 2017 by the authors.